Expanding the Diversity at the C-4 Position of Pyrido[2,3-d]pyrimidin-7(8H)-ones to Achieve Biological Activity against ZAP-70 - Victor Masip; Ángel Lirio; Albert Sánchez-López; Ana B. Cuenca; Raimon Puig de la Bellacasa; Pau Abrisqueta; Jordi Teixidó; José I. Borrell; Albert Gibert; Roger Estrada-Tejedor (MDPI AG, 2021)
Pyrido[2,3-d]pyrimidin-7(8H)-ones have attracted widespread interest due to their similarity with nitrogenous bases found in DNA and RNA and their potential applicability as tyrosine kinase inhibitors. Such structures, presenting up to five diversity centers, have allowed the synthesis of a wide range of differently substituted compounds; however, the diversity at the C4 position has mostly been limited to a few substituents. In this paper, a general synthetic methodology for the synthesis of 4-substituted-2-(phenylamino)-5,6-dihydropyrido[2,3-d]pyrimidin-7(8H)-ones is described. By using cross-coupling reactions, such as Ullmann, Buchwald-Hartwig, Suzuki-Miyaura, or Sonogashira reactions, catalyzed by Cu or Pd, we were able to describe new potential biologically active compounds. The resulting pyrido[2,3-d]pyrimidin-7(8H)-ones include N-alkyl, N-aryl, O-aryl, S-aryl, aryl, and arylethynyl substituents at C4, which have never been explored in connection with the biological activity of such heterocycles as tyrosine kinase inhibitors, in particular as ZAP-70 inhibitors.